Impact of China's financial development on the sustainable development goals of the Belt and Road Initiative participating countries - Li, Chenggang (2024)
China’s Belt and Road Initiative (BRI) aims to strengthen regional economic and policy cooperation and achieve the rapid development among the participating countries. While the impact on the financial development of the economic growth and energy environment of BRI participating countries has garnered close attention among scholars, few studies focus on the impact of financial development on the sustainable development goals (SDGs) of the BRI participating countries. To address this gap, we utilized panel regression models to quantitatively assess the impact of China’s financial development scale, structure, and efficiency on the SDGs of the BRI participating countries, and adopted Geographically and Temporally Weighted Regression (GTWR) model to explore the spatial-temporal effects of China’s financial development scale, structure, and efficiency on the SDGs of the BRI participating countries. Our findings indicate that China’s financial development has significantly promoted the SDGs of the BRI participating countries. This study further reveals that the scale and efficiency of China’s financial development have had a more pronounced impact on the SDGs of Asian countries, low- and middle-income countries, and the Land Silk Road participating countries, compared to those of European countries, high-income countries, and the Maritime Silk Road participating countries, respectively. In contrast, the structure of financial development primarily promotes the SDGs of European and high-income BRI participating countries in the land silk belt. The role of China’s financial development in promoting the SDGs of most BRI participating countries has gradually increased over time. This study provides valuable insights for decision-makers in China to facilitate the sustainable development of BRI participating countries and foster a shared community within the BRI framework.